2014
DOI: 10.3174/ajnr.a3849
|View full text |Cite
|
Sign up to set email alerts
|

MR Quantitative Susceptibility Imaging for the Evaluation of Iron Loading in the Brains of Patients with  -Thalassemia Major

Abstract: BACKGROUND AND PURPOSE:Patients with ␤-thalassemia require blood transfusion to prolong their survival, which could cause iron overload in multiple organs, including the heart, liver, and brain. In this study, we aimed to quantify iron loading in the brains of patients with ␤-thalassemia major through the use of MR quantitative susceptibility imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…We investigated hemispheric location, gender and age‐related effects on iron content in healthy East‐Asian adults using the QSM method. Regional iron levels ranking from the highest to the lowest were found in the globus pallidus, substantia nigra, red nucleus, caudate nucleus and putamen, and thalamus, which agreed well with published QSM studies that investigated healthy subjects and biochemical studies of postmortem brain tissue .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We investigated hemispheric location, gender and age‐related effects on iron content in healthy East‐Asian adults using the QSM method. Regional iron levels ranking from the highest to the lowest were found in the globus pallidus, substantia nigra, red nucleus, caudate nucleus and putamen, and thalamus, which agreed well with published QSM studies that investigated healthy subjects and biochemical studies of postmortem brain tissue .…”
Section: Discussionsupporting
confidence: 88%
“…It is reported that in deep gray matter a positive linear correlation exists between magnetic susceptibility and iron content measured using x‐ray fluorescence imaging . Clinically, promising results have also been shown in investigations of patients with β ‐thalassemia, multiple sclerosis and Parkinson's disease .…”
Section: Introductionmentioning
confidence: 97%
“…This is also supported by a study that showed evidence of iron overload in brain structures such as the putamen, dentate nucleus, substantia nigra and red nucleus of patients with beta-thalassemia[32]. Another group of patients with thalassemia also showed iron overload and increased oxidative damage[33].…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, a few MRI studies have suggested a possible brain tissue iron overload as a possible pathogenic mechanism of brain injury. However, using a dedicated MRI protocol and an advanced voxel‐based quantitative MRI analysis, no iron overload was observed in the brain tissue of beta‐thalassaemia patients, but in the choroid plexuses (Qiu et al , ), revealing that the blood brain barrier efficiently protects the central nervous system from the persistently high systemic iron levels that characterize beta‐thalassaemia. The present study went a step further and investigated possible relationships between cognitive performances and either the white matter abnormality burden on conventional MRI, the intracranial vessel changes on conventional MRA and the iron load quantified with a dedicated MRI protocol and subsequent advanced MRI analysis.…”
Section: Discussionmentioning
confidence: 99%